PENERAPAN PRINSIP HAKIM PASIF DAN AKTIF DALAM PROSES PEMBUKTIAN HUKUM ACARA PERDATA - Rizka Afi Aryana (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This article discusses the application of passive and active judge principles in the process of civil procedural law evidence in Indonesia. The principle of the passive judge emphasizes neutrality and objectivity, where the judge only considers the evidence presented by the parties. However, this approach can result in decisions that do not reflect substantial truth, especially in complex cases. On the other hand, the principle of an active judge allows judges to gather additional evidence and expedite the dispute resolution process, but it also risks creating bias. This research uses the juridical-normative method to analyze the interaction of both principles in legal practice, with the hope of providing insights into the dynamics of their application and its implications for the quality of law enforcement.